Stereotip Etnis Tionghoa dalam Film: Analisis Sosiologi Komunikasi pada Film Ngenest: Kadang Hidup Perlu Ditertawakan Karya Ernest Prakasa - Laksono, Puji; Rustanti, Rindu (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2024)
Ethnic Chinese are spread throughout the world, including in Indonesia. They have long been part of the diversity of the Indonesian nation, even before independence. The presence of the Chinese community in Indonesia has been integrated significantly and is considered an integral part of the identity of the Indonesian nation. The aim of this research is to find out how ethnic Chinese are stereotyped in the film Ngenest: Sometimes Life Needs to be Laughed at and to find the meaning and signs used by the film Ngenest: Sometimes Life Needs to be Laughed at in presenting Chinese ethnicity. The approach used is communication sociology with the theory used to solve this research is semiotic theory. The object of the research is the film Ngenest: Sometimes Life Needs to be Laughed at, which is an Indonesian film produced and broadcast in 2015 with a duration of 95 minutes. The method used in this research is a qualitative method using Roland Barthes' semiotic analysis technique. The results of the research show that there are several scenes depicting Chinese ethnic stereotypes in the film Ngenest: Sometimes Life Needs to be Laughed At. The character Ernest in this film is depicted as a character who often experiences unpleasant treatment or bullying in his environment. There are scenes where Ernest is clearly called derogatory names such as "Chinese", reflecting the differences in cultural background between Ernest and those around him. This film also breaks the stereotype that exists in society, that ethnic Tinghoa/Chinese descendants are deceitful, stingy and want to win for themselves. The Chinese ethnicity in this film is described by Ernest Prakasa that not all Chinese descendants have the same characteristics as society's perception of Chinese descendants.